Success Of Pulmonary Tuberculosis Treatment Services In Bangetayu Primary Healthcare Semaranga Reviewed From The Aspect Of Quality Of Service - Aisyah Lahdji (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTPulmonary tuberculosis is a disease that until now has a high morbidity rate, including in Indonesia. Indonesia ranks second with the highest TB burden in the world. From 2013 to 2016, the percentage of the success rate of treatment in Semarang City was 83%, where the lift was still below the target of 90% and in the health profile of the Bangetayu Primary Health Care Semarang, the cure rate was 55% and complete treatment was 34%. One of the controls in TB disease is treatment with the Directly Observed Treatment Short-Course (DOTS) system by monitoring medication. The existence of these efforts still cannot increase the success rate of TB treatment. The purpose of this study was to analyze the scope of achievement of the success of pulmonary TB treatment in Bangetayu Primary Health Care in terms of service quality aspects. This study included descriptive observational research with a qualitative approach. Data collection in this study used interviews and observations by determining the source with the snowball sampling method, namely the head of the health care, the person in charge of the P2P program, the holder of the pulmonary TB program and laboratory officer. This research was conducted at Bangetayu Primary Health Care in November 2018 to December 2018. Assessment of service quality is seen from the aspects of input, process and 5 dimensions of service quality. The results of the study found that the quality of management services from input, process and 5 dimensions of service quality at the Bangetayu Primary Health Care were good. The conclusion of this study is that the Bangetayu Primary Health Care has implemented TB service management well, even though the achievements of TB treatment have not met the target, so that the failure to achieve success in TB treatment in Bangetayu Primary Health Care, Semarang is not caused by health service factors.Keywords : Pulmonary tuberculosis, Bangetayu Primary Health Care, service qualityCorrespondence to : lahdjiaa@yahoo.com ABSTRAKTuberculosis Paru (TB Paru) adalah penyakit yang sampai saat ini memiliki angka kesakitan yang tinggi termasuk di Indonesia. Indonesia menduduki peringkat kedua dengan nilai beban TB tertinggi di dunia. Dari tahun 2013 hingga tahun 2016, presentase angka keberhasilan pengobatan di Kota Semarang sebesar 83%, dimana angkat tersebut masih berada dibawah target sebesar 90% . Pada profil kesehatan Puskesmas Bangetayu Semarang, didapatkan angka kesembuhan sebesar 55% dan pengobatan lengkap sebesar 34%. Salah satu pengendalian pada penyakit TB adalah pengobatan dengan system Directly Observed Treatment Short-Course (DOTS) dengan pemantauan minum obat. Adanya upaya tersebut masih belum bisa meningkatkan angka keberhasilan pengobatan TB secara optimal. Tujuan penelitian ini adalah untuk menganalisis capaian keberhasilan pengobatan TB paru di Puskesmas Bangetayu yang ditinjau dari aspek mutu pelayanan. Penelitian ini termasuk penelitian deskriptif observatif dengan pendekatan kualitatif. Pengumpulan data pada penelitian ini menggunakan wawancara dan observasi dengan penentuan narasumber dengan metode snowball sampling, yaitu kepala puskesmas, penanggungjawab program P2P dan pemegang program TB paru, petugas Laboratorium. Penelitian ini dilakukan di Puskesmas Bangetayu Semarang pada bulan November 2018 hingga Desember 2018. Penilaian mutu pelayanan dilihat dari aspek input, proses dan 5 dimensi mutu pelayanan. Hasil penelitian didapatkan bahwa mutu pelayanan manajemen dari input, proses dan 5 dimensi mutu pelayanan di Puskesmas Bangetayu Semarang sudah baik. Kesimpulan pada penelitian ini adalah Puskesmas Bangetayu sudah menerapkan manajemen pelayanan TB dengan baik, meskipun capaian keberhasilan pengobatan TB belum memenuhi target, sehingga ketidakberhasilan capaian keberhasilan pengobatan TB di Puskesmas Bangetayu, Semarang tidak disebabkan oleh faktor pelayanan kesehatan.Kata Kunci : TB Paru, puskesmas bangetayu, mutu pelayananKorespondensi : lahdjiaa@yahoo.com